2014
DOI: 10.1007/s40620-013-0033-0
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric nutritional risk index is a strong predictor of mortality in hemodialysis patients: data from the Riscavid cohort

Abstract: These results demonstrate that low GNRI (<92) is associated with malnutrition and is a strong predictor of overall mortality in HD patients. However, cardiovascular events did not differ among the GNRI quartiles. A low GNRI score can be considered a simple and reliable marker of malnutrition and predictor for mortality risk in Caucasian HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 22 publications
1
59
0
1
Order By: Relevance
“…Park et al [8] confirmed in Korean HD patients that GNRI may be a significant predictor of mortality. More recently, Panichi et al [16] have shown that the results of their study are closer to those of Yamada, and indicate that values lower than 92 may represent a strong indicator of unfavorable outcome in Caucasian HD patients.…”
Section: Discussionmentioning
confidence: 52%
“…Park et al [8] confirmed in Korean HD patients that GNRI may be a significant predictor of mortality. More recently, Panichi et al [16] have shown that the results of their study are closer to those of Yamada, and indicate that values lower than 92 may represent a strong indicator of unfavorable outcome in Caucasian HD patients.…”
Section: Discussionmentioning
confidence: 52%
“…Their results have been further confirmed by subsequent studies, especially from Asian chronic HD patients [8,11,21]. Besides that, studies from Italy, Netherlands and French also got similar conclusion [10,28,37]. Recently, a prospective cohort study with a total of 3436 Japanese HD participants included, Matsukuma et al demonstrated that lower GNRI levels are an independent risk factor for infection-related mortality and all-cause mortality in patients undergoing HD [32].…”
Section: Discussionmentioning
confidence: 72%
“…1,3 According to a recent European study, a low GNRI score can be considered a simple and reliable marker of malnutrition and a predictor for mortality risk in Caucasian HD patients. 2 According to another recent study, GNRI is a valid tool for the longitudinal assessment of nutritional status in HD patients. 11 Our previous study also showed similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…1 Panichi reported that lower GNRI is associated with malnutrition and it is a strong predictor of overall mortality in HD patients and other author reported that GNRI was a simple method for predicting nutritional status and clinical outcomes in PD patients. 2,3 Onodera et al first reported the validity of the Onodera's prognostic nutritional index (OPNI) in predicting the prognosis in 189 patients undergoing gastrointestinal surgeries. 4 The equation for the OPNI includes the serum albumin level and the total lymphocyte count (TLC).…”
Section: Recently Yamada Et Al Reported That Geriatricmentioning
confidence: 99%